A SEMANTIC ANALYSIS OF EMOTIONAL AND PERSUASIVE LANGUAGE IN MOTIVATIONAL SOCIAL MEDIA COMMENT - Nazwa Khalifatunnisa; Nasywa Kamilah; Annisa Fauziah; Tatu Siti Rohbiah (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2026)
Motivational content on social media has become increasingly prevalent; however, the ways in which language conveys emotions and persuades audiences in digital interactions remain underexplored. This study aimed to analyze the semantic meanings, emotional expressions, and persuasive language used in motivational social media comments on TikTok and Instagram. The data consisted of [N] comments collected between January and April 2026 through purposive sampling, focusing on comments containing emotional, motivational, and persuasive elements. Using a descriptive qualitative approach, the data were analyzed through semantic and pragmatic-semantic techniques to examine how meaning was constructed and interpreted in context. The findings revealed that emotional language dominated the comments, particularly in expressions of praise, empathy, and encouragement. In addition, persuasive meanings were frequently conveyed through motivational statements, analogies, and reflective expressions, which functioned as forms of implicit persuasion. The study also found that meaning was dynamic and shaped by contextual factors, audience perceptions, and communicative intentions. These results contribute to a more profound understanding of how language functions to construct meaning, express emotions, and influence audiences in digital communication environments.